Also on Kutnar and Marek‘s Dějepisectví - Kábová, Hana (Dějiny – teorie – kritika, 2010)
This paper responds in a discussive manner to a critical review by Miloš Havelka of the third edition of František Kutnar‘s and Jaroslav Marek‘s book Přehledné dějiny českého a slovenského dějepisectví, published in Dějiny – teorie – kritika 6/2009, pp. 380–387.